Three new species of Thaloe Brescovit (Araneae: Anyphaenidae: Anyphaeninae), with descriptions of the first known females of the genus - Brescovit, Antonio D.; Oliveira, Luiz Fernando M. (Zootaxa, 2019)
Three new species of the genus Thaloe are described from Antillean region: Thaloe maricao n. sp., from Maricao, Puerto Rico and Virgin Island, Thaloe leboulet n. sp., from Le Boulet and Mariani, Haiti and Thaloe ebano n. sp., from the Dominican Republic. Females of species of this genus are described for the first time.